THE DEVELOPMENT OF WORD CLUSTER - Khaydarova Nigora; Abdukhalimova Gulshoda (TADQIQOTLAR, 2025)
Annotation: This article explores the historical and theoretical development of word clusters, highlighting their significance in linguistic theory and practical applications such as computational linguistics, natural language processing, and language education. The research traces the evolution of the concept from early linguistic grouping practices to modern algorithmic approaches that leverage statistical and semantic analysis. Particular attention is given to the methodology of cluster formation, types of clustering algorithms, and the impact of word clusters on enhancing machine understanding of human language. The study also addresses the pedagogical value of word clusters in vocabulary acquisition and cognitive linguistics. The findings underline that the development of word clusters has been both a reflection of linguistic theory and a tool that continues to shape it.